Evaluation of Standard Space Size of Residential Unit, Residential Unit Kebon Kacang, Central Jakarta - Ulinata; Raja, Sion Lumban; Sitompul, Jibrael Jonathan; Purba, Rahmawani (International Journal of Science and Society, 2026)
As part of the history of vertical housing development in Indonesia, the government began construction of the first flats in 1981 with the Kebon Kacang Flats project in Jakarta. These flats pioneered the concept of vertical settlements designed for the general public. Since then, flat construction has continued to develop. The government and private developers are increasingly aggressively developing flats across various areas, especially in urban centers and commercial areas where land availability is under high pressure. Therefore, a deep understanding of the concept, function, and development of flats is essential for formulating a comfortable and effective apartment policy for the future of cities in Indonesia. However, in reality, there are often problems with the amount of space in an apartment unit, so it does not meet the minimum requirements for survival. The research entitled Evaluation of the Standard Size of the Space Standard of the Kebon Kacang Flats Residential Unit, Central Jakarta was carried out to measure whether the size of the space of the Kebon Kacang Flats, Central Jakarta, is in accordance with the standard of the size of the Apartment Housing Unit and the living needs of the residents. This research was conducted through field observation and data collection at the Kebon Kacang Flats residential unit in Central Jakarta.